HERMENEUTIKA ASGHAR ALI ENGINEER - Shirhi Athmainnah (As-Salam: Jurnal Studi Hukum Islam & Pendidikan, 2014)
The perspective of normativity is an understanding of religion which ismore oriented to the relation of human with God and focused to text studynot to submit the rational side. Whereas, historisity is how to understanda religion and text by understanding the historical sides that cover them,or socio-cultural tendencies that cover them too. This renewal of thingkingappears as a concern of the contemporary scientists which are taking notefor the diversity of moslem ………, so the thought above becames a theologicalrevolution toward tranformative theology to answer the reality nowadays.This thought is as a concern of Asghar Ali Engineer, a thinker from Indiafor making phenomenal changes from the perspective and characteristicof moslem.Asghar Ali Engineer by using hermeneutical approach, stresses toconsideration socio-history to find the general principle (substantive) inthe Al-Qur’an. More further, Asghar uses the arguments of ulama/thinkeras an effort to make his ideas stronger. Observating the contains freom text(Al’Qur’an or history) aims to be carrying a gender equality., that is oftenseen in others works. Asghar dissolve a text into context, in order text thathe concerns to this work, to find the relevancy, which is agreeing with thecondition of its era. This case is the evidence that Asghar is efforting to makes text of Al-Qur’an comes alive, so it is become the solution of any problempeople have.